Overall survival in advanced epidermal growth factor receptor mutated non-small cell lung cancer using different tyrosine kinase inhibitors in The Netherlands: a retrospective, nationwide registry studyResearch in context - Rolof G.P. Gijtenbeek; Ronald A.M. Damhuis; Anthonie J. van der Wekken; Lizza E.L. Hendriks; Harry J.M. Groen; Wouter H. van Geffen (The Lancet Regional Health. Europe, 2023)
Summary: Background: Clinical guidelines advise osimertinib as preferred first line treatment for advanced epidermal growth factor receptor (EGFR) mutated non-small cell lung cancer (NSCLC) with deletions in exon 19 (del19) or exon 21 L858R mutation. However, for first-line osimertinib the real world overall survival (OS) in mutation subgroups remains unknown. Therefore, the aim of this study was to evaluate the real-world OS of those patients treated with different generations of EGFR-tyrosine kinase inhibitors (TKI), and to identify predictors of survival. Methods: Using real-world data from the Netherlands Cancer Registry (NCR) we assessed patients diagnosed with stage IV NSCLC with del19 or L858R mutation between January 1, 2015, and December 31, 2020, primarily treated with then regularly available TKIs (including osimertinib). Findings: Between January 1, 2015, and December 31, 2020, 57,592 patients were included in the NCR. Within this cohort we identified 1109 patients, 654 (59%) with del19 and 455 (41%) with L858R mutations, respectively; 230 (21%) patients were diagnosed with baseline brain metastases (BM). Patients were treated with gefitinib (19%, 213/1109), erlotinib (42%, 470/1109), afatinib (15%, 161/1109) or osimertinib (24%, 265/1109). Median OS was superior for del19 versus L858R (28.4 months (95% CI 25.6–30.6) versus 17.7 months (95% CI 16.1–19.5), p < 0.001. In multivariable analysis, no difference in survival was observed between various TKIs in both groups. Only in the subgroup of patients with del19 and baseline BM, a benefit was observed for treatment with osimertinib. Interpretation: In this nationwide real-world cohort, survival of Dutch patients with advanced NSCLC and an EGFR del19 mutation was superior versus those harboring an L858R mutation. Osimertinib performed only better as first-line treatment in patients with del19 and BM. Funding: None.